Extraction of intracardiac and great vessels foreign bodies by means of catheterism - Tiscornia, Eduardo; Delgado, Alicia; Sálice, Mario; León, Isidro; Sojo, Enrique; Carriquiry, Luis; Alfonso, Ruben (Cirugía del Uruguay, 1984)
The author reports two cases of extraction of intracardiac and great vessels foreign bodies by means of catheterism. In author's opinion, extraction by the surgical method shoud not be attempted before having previously tried any of the interventionist radiological methods mentioned in this work. Very importan! is the use of radiopaque catheters Presentado en la Sociedad de Cirugía del Uruguay el 13 de abri I de 1983. Prof. Adj. de Radiología, Asistente de Radiología, Prof. Adj. de Radiología, Méd. Colaborador de Clínica Quirúrgica, Prof. Adj. de Clínica Quirúrgica, Ex-Asistente de Clínica Quirúrgica y Asistente de Radiología. Dirección: Brito del Pino 1323 Ap. 201, Montevideo. (Dr. E. Tiscornia). Op . Clínico de Radiolog/a (Director Prof. Dr. Andrés De Tenyi). Hospital de Clfnicas "Dr. Manuel Quinte/a". Facultad de Medicina, Montevideo. when performing parenteral or other type of alimenta• tion because in that way ii is possible to detecl same by X-ray if los! and extrae! them by percutaneous catheterism.